Effects of Polysaccharides From Auricularia auricula on the Immuno-Stimulatory Activity and Gut Microbiota in Immunosuppressed Mice Induced by Cyclophosphamide - Kong, Xianghui; Duan, Weiwen; Li, Dingjin; Tang, Xiaoxian; Duan, Zhenhua (Frontiers in Immunology, 2020)
Recently, the immuno-enhancing potential of polysaccharide from Auricularia auricula (AAP) has been an area of research interest. However, the immune-stimulatory activity and mechanisms of AAP in immunosuppressive mice treated with cyclophosphamide (CTX) are still poorly understood. This study aimed to evaluate the immuno-enhancing effects of AAP and mine its possible mechanisms. Firstly, polysaccharides were isolated from A. auricula and purified. Secondly, the immune-stimulatory activities of the first AAP fraction (AAP1) were evaluated in the CTX-treated mice. Results showed that AAP1 significantly enhanced immune organ indexes, remarkably stimulated IFN-γ, IL-2, IL-4, IL-10, and TNF-α levels in the serum, and dramatically up-regulated the mRNA levels of Claudin-1, Occludin and ZO-1. Compared to the CTX group, AAP1 administration restored the gut microbiota composition similar to that of the control group by decreasing the ratio of Firmicutes/Bacteroidetes and increasing the relative abundances of short-chain fatty acid-producing microbiota. This study provides useful information for its further application as an immune-stimulator in foods and drugs.